ANALISIS PERBEDAAN PERSEPSI ANTARA KONSUMENSWALAYAN INDOMARET DAN ALFAMART - Nur Setiawan, Andik Ika (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to find out if there is a difference in the perception of consumers of product, price, promotion and service between Alfamart and Indomaret supermarket in the village of Merjosari town of Malang. These studies collect data by using the questionnaire as many as 320 questionnaire, where the subject is the consumer Indomaret 160 160 Alfamart questionnaire and the questionnaire. Data analysis techniques using independent t test. From the test results that are obtained in terms of consumer products have the perception of Alfamart and Indomaret is the same, in terms of consumer prices Indomaret and Alfamart also has the same perception, in terms of consumer promotion for Indomaret and Alfamart has a different perception where Indomaret is reasonably give a better promotion than Alfamart, whereas in terms of service to consumers have the perception of Alfamart and Indomaret different where Alfamart is reasonably give better service than by Indomaret.Â Key Word : Indomaret, Alfamart, Perception, Consumers.